Utilisation of eight or more antenatal care visits and its associated socio-economic-related inequalities in sub-Saharan Africa: A decomposition analysis - Richard Gyan Aboagye; Augustus Osborne; Anayochukwu Edward Anyasodor; Sharon Vera Yikindi; Qorinah Estiningtyas Sakilah Adnani; Bright Opoku Ahinkorah (PLoS ONE, 2025)
Introduction Inadequate utilisation of maternal healthcare services, particularly antenatal care (ANC), poses a challenge in sub-Saharan Africa (SSA). There is a dearth of regional studies that address the socio-economic disparities in the use of ANC in SSA. Therefore, we examined the wealth and education-based inequalities in the utilisation of ANC services among women in SSA. Methods We analysed secondary data obtained from the Demographic Health Survey conducted in fifteen countries in SSA. We estimated the degree of wealth and education-related inequalities using concentration curves, concentration indices (CIX), and decomposition analysis, which identified the factors contributing to the disparities in the utilisation of ANC. All the analyses were conducted using Stata version 17.0 (Stata Corporation, College Station, TX, USA). Results The results revealed a significant socio-economic gap in utilising ANC in SSA. We found positive and statistically significant wealth index-related (CIX = 0.30; p-value < 0.0001) and education-based inequalities (CIX = 0.33; p-value < 0.0001) in eight or more ANC visits. The extent of wealth index-related and education-based inequalities varied across the fifteen countries. The decomposition analysis showed that educational attainment accounted for about 21% of the inequalities in eight or more ANC visits. Wealth index contributed 12.14% of the inequalities in eight or more ANC visits. Our results further showed that women's education, wealth, parity, and place of residence significantly contributed to the utilisation of eight visits or more among women in SSA. Conclusion This study shows the disparities in ANC coverage, contingent upon wealth index and educational attainment. Our study highlights the importance of adopting a holistic approach involving robust cooperation between healthcare and other social service sectors. It is crucial to prioritise the primary social factors contributing to disparities in the utilisation of ANC services, including women’s education, parity, place of residence, and economic status. Policymakers and stakeholders must prioritise efforts to combat obstacles to healthcare access, including the provision of easily accessible, affordable, and culturally appropriate services.